Accurate stopping power calculations for antiprotons and protons - Bailey, J.; Kadyrov, Alisher; Abdurakhmanov, Ilkhom; Avazbaev, S.; Fursa, Dmitry; Bray, Igor (2015)
© Published under licence by IOP Publishing Ltd. The convergent close-coupling method is applied to calculate antiproton and proton stopping cross sections for atomic and molecular targets. Excellent agreement with experimental measurements is obtained for antiprotons in helium while unexpectedly large disagreement is found for the hydrogen molecule, which is inconsistent with very good agreement between our ionisation cross section and the experiment.